The IMF and the Silent Revolution : Global Finance and Development in the 1980s - Boughton, James (International Monetary Fund, 2000)
This pamphlet is adapted from Chapter 1 of Silent Revolution: The International Monetary Fund, 1979-89, by the same author. That book is full of history of the evolution of the Fund during 11 years in which the institution truly came of age as a participant in the international financial system.